Pembangunan Sistem Informasi Manajemen Toko menggunakan Telegram Bot berbasis Web (Studi Kasus Noor Electric) - Muhammad Hafizh Andifaisa; Djoko Pramono; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Noor Electric is a store in Malang that sells electrical equipment. Since the store was founded, the store has recorded transactions manually and manually recorded monthly reports using excel. Transaction data information in stores is also scattered in several places so that store owners find it difficult to collect transaction data. With these problems, a store management information system was created. The information system is built on two platforms, a web-based system and Telegram bots that make it easy for store owners to manage stores via the web or Telegram bots. Development of the system was conducted using the waterfall model and the MVC (Model View Controller). The system is built using the PHP language using Laravel as a web framework and BotMan as a Telegram bot framework with MySQL as the database used. The web-based system is accessed locally and the Telegram bot is accessed via the Telegram application using Ngrok to expose local data to the internet. The results of the requirements engineering analysis resulted in 19 functional requirements and one non-functional requirement. Functional testing is carried out by validation test using 19 test procedures with the results of all test procedures producing valid data. Another test is to use User Acceptance Testing by giving 16 statements with the results obtained in the agree/good category according to the Likert scale with a value of 78.75%. With this test, the information system is ready to be used by Noor Electric shop owners